Global Transcriptional Profiling of the Cyanobacterium Chlorogloeopsis fritschii PCC 9212 in Far-Red Light: Insights Into the Regulation of Chlorophyll d Synthesis - Ho, Ming-Yang; Bryant, Donald A. (Frontiers in Microbiology, 2019)
Some terrestrial cyanobacteria can acclimate to and then utilize far-red light (FRL; λ = 700–800 nm) to perform oxygenic photosynthesis through a process called Far-Red Light Photoacclimation (FaRLiP). During FaRLiP, cells synthesize chlorophylls (Chl) d and Chl f and extensively remodel their photosynthetic apparatus by modifying core subunits of photosystem (PS)I, PSII, and the phycobilisome (PBS). Three regulatory proteins, RfpA, RfpB, and RfpC, are encoded in the FaRLiP gene cluster; they sense FRL and control the synthesis of Chl f and expression of the FaRLiP gene cluster. It was previously uncertain if Chl d synthesis and other physiological and metabolic changes to FRL are regulated by RfpABC. In this study we show that Chl d synthesis is regulated by RfpABC; however, most other transcriptional changes leading to the FRL physiological state are not regulated by RfpABC. Surprisingly, we show that erythromycin induces Chl d synthesis in vivo. Transcriptomic and pigment analyses indicate that thiol compounds and/or cysteine proteases could be involved in Chl d synthesis in FRL. We conclude that the protein(s) responsible for Chl d synthesis is/are probably encoded within the FaRLiP gene cluster. Transcriptional responses to FRL help cells to conserve and produce energy and reducing power to overcome implicit light limitation of photosynthesis during the initial acclimation process to FRL.